Pengaruh Harga Emas, Suku Bunga dan Nilai Tukar Rupiah Terhadap Indeks Harga Saham Gabungan di Indonesia - Budiman, Dedi; Munir Hidayat, Asep; Tejaarief, Billy; Kenedi, Kenedi; Wulan Agustini, Anti (Journal of Business and Economics Research (JBE), 2025)
The main problem in the Indonesian capital market is the high volatility of the Jakarta Composite Index (JCI), which is often influenced by both external and internal factors, making it difficult for investors to make investment decisions. This uncertainty raises questions about the extent to which macroeconomic variables, particularly gold prices, interest rates, and the rupiah exchange rate, affect the movement of the JCI. The Jakarta Composite Index (JCI) is the primary indicator reflecting the performance of the Indonesian stock market. Its movement is heavily influenced by various macroeconomic variables, including gold prices, interest rates, and the rupiah exchange rate. Gold serves as a safe-haven asset favored during periods of market instability, while interest rates and exchange rates reflect monetary conditions and domestic purchasing power. This study aims to analyze the effect of gold prices, interest rates, and the rupiah exchange rate on the Jakarta Composite Index (JCI) in Indonesia. The method used is a quantitative approach with quarterly time series data from 2014 to 2024. The analysis was conducted using the Autoregressive Distributed Lag (ARDL) model with the assistance of EViews 12 software. The estimation results of the ARDL model show that in the short run, gold prices, interest rates, and the rupiah exchange rate do not have a significant effect on the JCI, as the t-statistic values of each variable are smaller than the t-table at a 5% significance level. However, in the long run, gold prices and the rupiah exchange rate have a significant effect on the JCI with t-statistic values of 2.984417 and 2.634944, respectively, which exceed the t-table. This indicates that movements in gold prices as a safe-haven asset and fluctuations in the exchange rate contribute to JCI dynamics in the long run. Conversely, interest rates show no significant effect in either the short run or the long run. These findings emphasize the importance of considering certain macroeconomic variables in the long run as a basis for investment decision-making in the Indonesian capital market. Therefore, stable and predictable macroeconomic policies are essential to create a healthy investment climate in Indonesia.